2024
DOI: 10.1037/dhe0000433
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond college: STEM college seniors on entering the workforce and the impact of race and gender.

Abstract: While a strong literature base exists around undergraduate experiences in Science, Technology, Engineering, and Math (STEM), few studies examine how students approach the question of “what’s next” after graduation. This study examines the impact of social ties on STEM college seniors’ plans to enter the STEM workforce, and how race/ethnicity and gender impact postgraduation planning in STEM. We interviewed a racially diverse sample of 39 STEM college seniors at a predominantly White research institution. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Thus, participants’ (and salient others’) behaviors were shaped by their meaning making of the environment and social identities of those around them, especially based on gender, race/ethnicity, and age. Consistent with prior research, shared identities provided a sense of comfort and connection (Lapan & Smith, 2023; Park et al, 2022; Smith & Gayles, 2018). In particular, participants appreciated having access to women managers and colleagues, as gender served as an easy talking point.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Thus, participants’ (and salient others’) behaviors were shaped by their meaning making of the environment and social identities of those around them, especially based on gender, race/ethnicity, and age. Consistent with prior research, shared identities provided a sense of comfort and connection (Lapan & Smith, 2023; Park et al, 2022; Smith & Gayles, 2018). In particular, participants appreciated having access to women managers and colleagues, as gender served as an easy talking point.…”
Section: Discussionsupporting
confidence: 80%
“…While engineering graduates are more likely than other STEM graduates to enter related careers (Sassler et al, 2017), not all engineering majors build careers in engineering. Broadly, STEM undergraduates’ career trajectories are shaped by many factors, including strong (e.g., family and peer) and weak social ties (e.g., relationships from conferences and the career center; Park et al, 2022). Specific to internships, Park et al (2022) found that same-race and/or same-gender mentors in STEM internships served as possibility models and sources of affirmation for women and Students of Color.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…As SOCs enter the STEM workforce, culture continues to shape their experiences and departure from STEM. For example, Park et al (2022) highlight how STEM SOCs experience racism and sexism during internships and show them which jobs and environments to avoid upon entering the workforce. Similarly, Strayhorn and Johnson (2016) find that SOCs are often ignored, overlooked, and assigned menial tasks during internships exposing students early on to the STEM workforce culture.…”
Section: Literature Reviewmentioning
confidence: 99%